Engineering Nanopatterned Structures to Orchestrate Macrophage Phenotype by Cell Shape - Kai Li; Lin Lv; Dandan Shao; Youtao Xie; Yunzhen Cao; Xuebin Zheng (Journal of Functional Biomaterials, 2022)
Physical features on the biomaterial surface are known to affect macrophage cell shape and phenotype, providing opportunities for the design of novel “immune-instructive” topographies to modulate foreign body response. The work presented here employed nanopatterned polydimethylsiloxane substrates with well-characterized nanopillars and nanopits to assess RAW264.7 macrophage response to feature size. Macrophages responded to the small nanopillars (SNPLs) substrates (450 nm in diameter with average 300 nm edge-edge spacing), resulting in larger and well-spread cell morphology. Increasing interpillar distance to 800 nm in the large nanopillars (LNPLs) led to macrophages exhibiting morphologies similar to being cultured on the flat control. Macrophages responded to the nanopits (NPTs with 150 nm deep and average 800 nm edge-edge spacing) by a significant increase in cell elongation. Elongation and well-spread cell shape led to expression of anti-inflammatory/pro-healing (M2) phenotypic markers and downregulated expression of inflammatory cytokines. SNPLs and NPTs with high availability of integrin binding region of fibronectin facilitated integrin β1 expression and thus stored focal adhesion formation. Increased integrin β1 expression in macrophages on the SNPLs and NTPs was required for activation of the PI3K/Akt pathway, which promoted macrophage cell spreading and negatively regulated NF-κB activation as evidenced by similar globular cell shape and higher level of NF-κB expression after PI3K blockade. These observations suggested that alterations in macrophage cell shape from surface nanotopographies may provide vital cues to orchestrate macrophage phenotype.